Efficacy and Safety of the New Appetite Suppressant, Liraglutide: A Meta-Analysis of Randomized Controlled Trials - Moon, Shinje (Endocrinol Metab (Seoul), 2021)
BACKGROUND: Obesity is a chronic disease associated with metabolic diseases such as diabetes and cardiovascular disease. Since the U.S. Food and Drug Administration approved liraglutide as an anti-obesity drug for nondiabetic patients in 2014, it has been widely used for weight control in overweight and obese people. This study aimed to systematically analyze the effects of liraglutide on body weight and other cardiometabolic parameters. METHODS: We investigated articles from PubMed, EMBASE, and the Cochrane Library to search randomized clinical trials that examined body weight changes with liraglutide treatment. RESULTS: We included 31 studies with 8,060 participants for this meta-analysis. The mean difference (MD) between the liraglutide group and the placebo group was −4.19 kg (95% confidence interval [CI], −4.84 to −3.55), with a −4.16% change from the baseline (95% CI, −4.90 to −3.43). Liraglutide treatment correlated with a significantly reduced body mass index (MD: −1.55; 95% CI, −1.76 to −1.34) and waist circumference (MD: −3.11 cm; 95% CI, −3.59 to −2.62) and significantly decreased blood pressure (systolic blood pressure, MD: −2.85 mm Hg; 95% CI, −3.36 to −2.35; diastolic blood pressure, MD: −0.66 mm Hg; 95% CI, −1.02 to −0.30), glycated hemoglobin (MD: −0.40%; 95% CI, −0.49 to −0.31), and low-density lipoprotein cholesterol (MD: −2.91 mg/dL; 95% CI, −5.28 to −0.53; MD: −0.87% change from baseline; 95% CI, −1.17 to −0.56). CONCLUSION: Liraglutide is effective for weight control and can be a promising drug for cardiovascular protection in overweight and obese people.